Fast drying of high-alumina MgO-bonded refractory castables. Issue 8 (1st June 2020) - Pinto, V.S.; Fini, D.S.; Miguel, V.C.; Pandolfelli, V.C.; Moreira, M.H.; Venâncio, T.; Luz, A.P.
Abstract: Refractory producers face many challenges in terms of producing MgO-containing castables due to the high likelihood of magnesia to hydrate in contact with water, resulting in Mg(OH)2 generation. The expansive feature of this transformation affects the performance of such refractories, as (i) if this hydrated phase is not accommodated in the formed microstructure, ceramic linings with cracks and low green mechanical strength will be obtained; and (ii) if crack-free pieces are prepared, they should present low porosity and reduced permeability, which require special attention when heating these materials. In both cases, spalling/explosion may be favored during the drying step of MgO-containing compositions. Hence, this work investigated the ability of various additives in the optimization of the drying behavior of Al2 O3 –MgO castables. Vibratable compositions were tested after incorporating polymeric fibers (PF), an organic salt (OAS), SiO2 -based additive (SM) or permeability enhancing active compound (MP) into the dry-mixtures. Various experimental measurements were performed to infer the role of the drying agents to prevent the samples' explosion and whether they would also influence other properties of the castables. As observed, OAS and MP helped to inhibit the MgO-bonded samples' explosion even under severe heating conditions (2–20 °C/min) and increased their green mechanical strength and slag infiltration resistance when compared to the additive-free composition. On the other hand, the addition of polymeric fibers (PF) or silica-based compound (SM) to the formulations was not able to prevent the castables' explosion when using a high heating rate and other side effects (samples' cracking during drying at 110 °C, high linear expansion and increased slag penetration during corrosion tests) could also be observed when testing these materials. Thus, the selection of suitable drying agents is a key issue, as they may allow the development of MgO-bonded castables with enhanced properties and lower spalling risk during their first thermal treatment.